The Role Of Stakeholder In Developing Sustainable Island Nature Base Tourism In Tatoareng Sangihe North Sulawesi - Mozes, Getruida Nita; Darma Putra, I Nyoman; Sudiarta, I Nyoman; Kristianto, Yohanes (Jayapangus Press, 2025)
Development of sustainable nature-based tourism in the islands requires the role of stakeholders who not only support environmental, local economic and cultural sustainability but also enhance the tourist experience and their satisfaction. This research focuses on identifying the existing conditions of tourism development in the Tatoareng Islands, and the role of stakeholder in developing nature-based island tourism in Tatoareng Sangihe, North Sulawesi. This research uses a descriptive qualitative approach. Data collection techniques include observation, interviews, focus group discussions, and document study. Data reduction techniques and SWOT analysis were used to analyze the data. The findings show that the Tatoareng Islands have potential tourist attractions, including protected habitats, wildlife and cultural heritage. However, there are several challenges in their development, such as limited accessibility, infrastructure, and low tourism human resource quality. The role of stakeholders is vital in improving the quality of the 4A components (attractions, amenities, access, and ancillary services) and enhancing the tourism human resources of the local community to achieve sustainable nature-based tourism development goals in Tatoareng.